Por detrás da fala: a comunicação de más notícias na perspectiva de médicos e familiares - Monteiro, Daniela Trevisan (2013)
Bad news in the hospital scenario creates difficulties for professionals who need to accomplish this task. But, also, it is a difficult time and that changes the perspective of patients and their families about their future. Faced with this assumption, the research that led to this thesis aimed to understand the process of bad news communication in the context of the Intensive Care Unit for adults, from the perspective of physicians and family members involved in the hospitalization. This is a qualitative study of an exploratory and descriptive nature, covering all 23 participants, including 12 doctors, working in the Intensive Care Unit of a teaching hospital in the interior of Rio Grande do Sul, and 11 family members of patients admitted in this unit. We interviewed all doctors working in the unit, while the number of family participants was achieved by the criterion of sample saturation. We used semi-structured interviews and non-participant observation to collect the information, which was analyzed from the content analysis. The categories of information coming from the analysis were described and discussed in two articles that make up the essence of this work. The results show that each doctor search, in line with your style, a way of communicating based on personal experience and common sense. Both the lack of formation as the difficulty of dealing with suffering and death are related to the difficulty in communicating bad news by the doctor, giving it the need to exclude the feelings, coming from the hospital routine through the use of mechanisms aimed at appeasement of emotions. One should also consider that the family is in a moment of anguish, which can cause difficulty in understanding the information given by the doctors. Based on these appointments is considered that, in the doctor/family relationship the communication is even more technical and prioritizes unique clarifications the disease and treatment. The doctors did not feel prepared to communicate, and especially to listen to the suffering. But one should also consider how the families are underserved.